Teachers’ professional development on student achievement: perceptions of district superintendents of schools in USA - Prakasha, G. S.; Grundmeyer, Trent; Arulnesan, Sivaselwam; Bahubali, G. P.; Sangtam, Yolila (Journal of Education and Learning (EduLearn), 2025)
The perceptions of school superintendents on planning and designing of school teachers’ professional development programmes (PDP) place a crucial role in inservice teacher development. The present study aimed to examine the school superintendents’ perceptions towards professional development of teachers based on students’ academic achievement. The study employed quantitative descriptive research design which included descriptive and inferential statistics to interpret the superintendents’ perceptions on teachers’ professional development plan. The researchers utilized quntitiatve surveys to gather data from 128 public school superintendents and captured their perceptions on Teachers PDPs. Findings reported that superintendents’ perceived PDPs must integrate knowledge on student achievemet, skills needed, and worthwhile-content mastery. Study further revealed that, students’ academic achievement details can provide accurate components to be included in teachers PDP. Future researchers may explore the evidence-based planning of PDPs to motivate the teachers’ active participation in professional growth activities.